Polymerase chain reaction localization of constitutive nitric oxide synthase and soluble guanylate cyclase messenger RNAs in microdissected rat nephron segments. - Terada, Y (1992)
Stimulation of the release of nitric oxide (NO) in the kidney has been shown to result in renal hemodynamic changes and natriuresis. NO is a potent stimulator of soluble guanylate cyclase, leading to an increase of cyclic GMP. The precise localization of NO synthase and soluble guanylate cyclase in the renal structure is not known. In this study, the microlocalization of mRNAs coding for constitutive NO synthase and soluble guanylate cyclase was carried out in the rat kidney, using an assay of reverse transcription and polymerase chain reaction in individual microdissected renal tubule segments along the nephron, glomeruli, vasa recta bundle, and arcuate arteries. A large signal for constitutive NO synthase was detected in inner medullary collecting duct. Small signals were detected in inner medullary thin limb, cortical collecting duct, outer medullary collecting duct, glomerulus, vasa recta, and arcuate artery. Soluble guanylate cyclase mRNA is expressed largely in glomerulus, proximal convoluted tubule, proximal straight tubule, and cortical collecting duct, and in small amounts in medullary thick ascending limb, inner medullary thin limb, outer medullary collecting duct, inner medullary collecting duct, and the vascular system. Our data demonstrate that NO can be produced locally in the kidney, and that soluble guanylate cyclase is widely distributed in glomerulus, renal tubules, and the vascular system.